Geoelectrical Resistivity and Hydrogeochemical Contrast between the Area that Has BeenApplied with Fertilization for Long Duration and Non-Fertilization - Islami, Nur (ITB Journal Publisher, LPPM ITB, 2010)
Integrated geoelectrical resistivity, hydrogeochemical and soil properties analysis methods were used to study the area that has been applied with fertilization for long duration and non-Fertilization in Machang, North Kelantan. The Machang plain is covered with Quaternary fluvial sediments overlying granite bedrock. The drainage system is dendritic with the main river flowing into the South China Sea. In this study, the area was divided into two sites. Site-1 is the non-fertilized site, and Site-2 is the regularly-fertilized site. At shallow depth from the surface to depths of 75 cm a lower average geoelectrical resistivity values were obtained from the regularly fertilized site which has not been fertilized for the last ten months prior to the survey. The average resistivity values were around 0.366 times less in unfertilized sites. Residual nitrate and chloride were still present at the regularly chemically fertilized sites. At sites where no chemical fertilizer was added, the nitrate and chloride concentration were also found. These are due to the faces excretion of from the farm animals. The presence of nitrate and chloride content in pore water reduced the resistivity values. Thus despite low moisture content, the resistivity values to remain low. Normally, resistivity values are inversely proportional to moisture content for area with similar soil condition.Â